Analysis of heritability and correlation of agronomic character towards the yield of several m6 generation of wheat mutants (Triticum aestivum L.) in the lowlands. Issue 1 (April 2020) - Farid BDR, M; Nasaruddin,; Iswoyo, H; Ridwan, I; Arsyad, F
Abstract: This research aims to find out the lowland and high production adaptive M6 generation of mutant wheat, to know the positive correlation between growth parameters and production components on yields, and to determine the parameters that have high heritability. The research was carried out in the Bonto Parang which is located in Kelara Village, Tolo Selatan District, Jeneponto Regency at an altitude of 135 m asl, with coordinates of 5 ° 24'58.0 "LS 119 ° 54'58.2" BT, Climate type E (2 wet months and 5 months dry) andosol soil type. The research was conducted from July to October 2018. This research used a Randomized Block Design with 16 lines as genetic material resulting from mutations and four varieties (Dewata, Selayar, Nias, and Munal) used as a comparison so that there were 20 genotypes. The research was conducted with 3 replications so that there were 60 experimental units. The results showed that the M6 mutant wheat is adaptive to lowland and it has a high number of products which is N 350 3.8.9 (3.48 tons.ha-1), N 200 2.4.B.6 (3.37 tons.ha-1) and N 300 4.3.6 (2.71 ton.ha-1). Growth parameters and production components that have a significant positive correlation and bring significant results are plant height, number of tillers, productive tillers, number of stomata, stomatal density, chlorophyll index, panicle length, number of spikelet scales, percentage of empty floret, weight of seed scales and of 1000 seeds, high heritability and high genetic diversity followed by the characteristics of productive tillers, number of seedlings, scum production, clump production, production and flowering age.